Demonstration of the use of a photosynthetic microbial fuel cell as an environmental biosensor. (2017) - Labro, Julie; Craig, Timothy; Wood, Susanna A.; Packer, Michael A.
Microbial fuel cells (MFCs) are bioelectrochemical systems (BESs) that exploit biological catalytic processes for the generation of electrical power or the accumulation of useful compounds. Photosynthetic MFCs (pMFCs) are those that utilise photosynthetic microorganisms, such as algae and cyanobacteria, to provide reducing power at the anode. A reproducible light-dependent electrogenic effect occurs as algae or cyanobacteria convert light to electrical energy in the BES. In addition to the generation of electricity, the phenomenon may be useful in niche circumstances such as for bioelectrosynthesis or for use in environmental biosensors. In this study we measure the effect of common toxicants (copper, thallium, zinc and glyphosate) on the electrogenic activity of electrode surface-dwelling algae and cyanobacteria. We observed a decrease in the light-dependent electrical response via these photosynthetic microorganisms in our pMFC that was proportional to the concentration of toxicants. This demonstrates the utility of these BESs as potential environmental biosensors where the metabolism of photosynthetic microorganisms acts to sense signals from the environment.